The Correlation Between Students’ Reading Speed and Their Reading Comprehension in Narrative Text at the Ninth Grade of SMPN 1 Ampek Angkek - Sy, Suci Triana Putri; Kardena, Absharini; Eliza, Eliza; Dewi, Merry Prima (Education Achievement: Journal of Science and Research, 2025)
This research was due to the problems that were found in SMPN 1 Ampek Angkek. The problems that were found were that students had difficulty in understanding the text, lack of vocabulary, and students were slow reader. Furthermore, the researcher also found that students who read slow scored higher than the students who read fast in reading comprehension. This research was quantitative research. The design of this research was correlational research. The researcher used two variables which they were variables X and variable Y. Variable X was students’ reading speed and variable Y was students’ reading comprehension. The researcher used cluster random sampling technique in this study. This means that the sample was taken randomly based on the class, and class IX 2 and IX 5 were chosen as the sample. There were 51 sample. For the method, the researcher asked the students to read the text. While the students were reading the text, the researcher counted the time by using a stopwatch. After collecting data, then the researcher analyzed students reading speed and the number of correct on the reading comprehension test. Furthermore, the correlation test was done by using SPSS. It was done to see whether there was a correlation between students’ reading speed and their comprehension. Based on the findings and discussions in this research, there were 3 finding of this research. First, there was no significant correlation between reading speed and reading comprehension. Second, there was positive correlation between two variables. Third, the correlation magnitude between two variables was low.  It can be concluded that this study against the theory that said close relationship between reading speed and reading comprehension. The data revealed that students with a high level of reading comprehension do not always have a high reading speed, and vice versa.